(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This thesis analyzes the role of artificial intelligence and data analysis technologies in improving the risk management system in customs activities. Based on international experience, practical problems in the customs system of Uzbekistan and ways to overcome them are identified and proposals are developed.